Decision Support for Investments in Sustainable Energy Sources Under Uncertainties - Kenneth Ian Talosig Batac; Angelie Azcuna Collera; Resy Ordona Villanueva; Casper Boongaling Agaton (International Journal of Renewable Energy Development, 2022)
Investment in sustainable energy sources is one of the climate mitigation strategies that can significantly reduce greenhouse gas emissions in the energy sector. However, in developing countries, investment is challenged by high capital expenditures and several uncertainties. This paper aims to provide decision support for investment in sustainable energy projects by evaluating the comparative attractiveness of shifting energy sources from fossil fuels to renewables and nuclear. Applying the real options approach (ROA), this paper calculates the value of the flexibility to postpone the investment decision and identifies the optimal timing (described here as the trigger price of coal) for shifting to sustainable energy sources. Then, various uncertainties are considered, such as coal and electricity prices, negative externality of using fossil fuels, and the risk of a nuclear accident, which are modelled using geometric Brownian motion, Poisson process, and Bernoulli probability. Applying the ROA model in the case of the Philippines, results find that investing in sustainable energy is a better option than continuing to use coal for electricity generation. However, contrary to conventional option valuation result that waiting is a better strategy, this study found that delaying or postponing the investment decisions may lead to possible opportunity losses. Among the available sustainable energy sources, geothermal is the most attractive with trigger prices of coal equal to USD 49.95/ton, followed by nuclear (USD 58.55/ton), wind (USD 69.48/ton), solar photovoltaic (USD 72.04/ton), and hydropower (USD 111.14/ton). Also, the occurrence of jump (extreme) prices of coal, raising the current feed-in-tariff, and considering negative externalities can decrease the trigger prices, which favor investments in sustainable energies. Moreover, the risk of a nuclear disaster favors investment in renewable energy sources over nuclear due to the huge damage costs once an accident occurs. Results provide bases for policy recommendations toward achieving a more secure and sustainable energy sector for developing countries that are highly dependent on imported fossil fuels.